2010
DOI: 10.1007/s12154-010-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and biological activities of 3-alkyl pyridinium polymeric analogues of marine toxins

Abstract: Two new large poly-1,3-dodecylpyridinium salts, APS12 and APS12-2 of 12.5-and 14.7-kDa size, respectively, were synthesised and tested for their pore-forming and transfection capabilities in HEK 293 and undifferentiated mouse ES cells using patch-clamp recording, Ca 2+ imaging and flow cytometry. Polymerisation reactions were enhanced by microwaves, and the product sizes were controlled by altering the irradiation time. This method can also be applied to obtain polymers with variable linking chains as shown by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…This water-soluble compound has a molecular weight of 11.9 kDa and is stable at room temperature [29]. For the current experiments, a stock concentration of 10 mg/mL APS8 in deionized water was kept at 4 °C and further diluted in cell culture media upon use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This water-soluble compound has a molecular weight of 11.9 kDa and is stable at room temperature [29]. For the current experiments, a stock concentration of 10 mg/mL APS8 in deionized water was kept at 4 °C and further diluted in cell culture media upon use.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the potential utility of poly-APS like compounds as anti-cancer agents, a series of synthetic analogs were prepared [29]. Preliminary results, demonstrated in this paper, revealed that at least one of these compounds, the 11.9 kDa analog APS8 (Figure 1), is a very potent α7 nAChR antagonist.…”
Section: Introductionmentioning
confidence: 98%
“…Future work needs to establish in more detail (1) the time course of tauopathy over longer periods; (2) quantitatively what levels of Tau are achieved and how far the injection spreads within CA1; (3) what Tau species (oligomeric or fibrils or others) are generated within the cell and how they are modulated by phosphorylation; (4) optimisation of intracellular delivery may further be achieved by synthetic Poly-APS with preselected polymeric length (as recently described [124]). In addition, Poly-APS-mediated intracellular macromolecule delivery should be exploited in greater detail as it provides high flexibility for (1) the region of administration, (2) the Tau species or gene construct of interest that is delivered (for example mutant or wild type; full length or truncated), (3) enables the coadministration of other disease-related toxins (for example synuclein, amyloid, etc.…”
Section: Further Application Of Poly-aps-mediated Taumentioning
confidence: 99%
“…Natural alkylpyridinium polymers (polyAPS), isolated from the marine sponge Haliclona [ Rhizoniera ] sarai [ 25 ] have several biological activities, including acetylcholinesterase inhibition [ 26 , 27 ]. Based on these natural polyAPS, synthetic alkylpyridinium compounds with similar structural and functional properties have been synthesized [ 28 , 29 ]. One of these analogs, APS8 ( Figure 1 ) binds to the α7 nAChR and completely blocks its activity at 1–3 nM APS8, but is less effective in blocking the α4β2 nAChR.…”
Section: Introductionmentioning
confidence: 99%